2020
DOI: 10.1016/j.actamat.2020.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of core–shell particle formation in drop-tube processed metastable monotectic alloys

Abstract: This is a repository copy of Dynamics of core-shell particle formation in drop-tube processed metastable monotectic alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Although we have unveiled that BCC dendritic growth occurs in powders d < 212 µm in size, measuring the undercooling required for this growth condition is not possible during drop-tube experiments. However, it has previously been estimated that the undercooling of Co-Cu droplets of similar size, based on the kinetics of monotectic liquid phase separation, is 210-250 K [40]. This value is in-line with the undercooling observed to mediate the order-disorder transformation in other materials [40].…”
Section: Resultssupporting
confidence: 64%
“…Although we have unveiled that BCC dendritic growth occurs in powders d < 212 µm in size, measuring the undercooling required for this growth condition is not possible during drop-tube experiments. However, it has previously been estimated that the undercooling of Co-Cu droplets of similar size, based on the kinetics of monotectic liquid phase separation, is 210-250 K [40]. This value is in-line with the undercooling observed to mediate the order-disorder transformation in other materials [40].…”
Section: Resultssupporting
confidence: 64%
“…Mechanism of formation and characteristics of these microstructures in drop tube processed 50 at. % Co alloy is available in literature [12,13]. Other researchers have also reported that the alloy is dendritic and that LPS is only feasible in the alloy at higher degree of undercooling [2,8,9].…”
Section: Takedownmentioning
confidence: 99%
“…When the uniform immiscible alloy melt is cooled into the miscibility gap of the component, the evolution of the microstructure in liquid-liquid phase transformation is the result of the interaction of droplet nucleation, diffusion growth/coarsening [33,34], spatial migration and the resulting collision and coagulation and two-phase separation [35,36]. The solidification pathways in immiscible Cu-Co alloy with different undercoolings were systematically expounded by Wei at al.…”
Section: The Solidification Process Of Immiscible Alloymentioning
confidence: 99%